2016
DOI: 10.1016/j.gene.2015.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic studies of the Red Sea

Abstract: Metagenomics has significantly advanced the field of marine microbial ecology, revealing the vast diversity of previously unknown microbial life forms in different marine niches. The tremendous amount of data generated has enabled identification of a large number of microbial genes (metagenomes), their community interactions, adaptation mechanisms, and their potential applications in pharmaceutical and biotechnology-based industries. Comparative metagenomics reveals that microbial diversity is a function of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 61 publications
(56 reference statements)
2
36
0
Order By: Relevance
“…Consequently, diverse Red Sea associated microbiomes have been the focus of several recent studies at KAUST, including those from different environments: mangrove sediment (Al-Amoudi et al 2016a; Al-Amoudi et al 2016b; Alzubaidy et al 2016; Simões et al 2015), sea water (Qian et al 2011; Jimenez-Infante et al 2016), coral (Bayer et al 2013), sponge (Gao et al 2015; Tian et al 2014), and extreme niches such as Red Sea brine pools (Mwirichia et al 2016; Zhang et al 2015; Kamanda Ngugi et al 2015; Siam et al 2012; Abdallah et al 2014; Antunes et al 2015; Behzad et al 2016; Jimenez-Infante et al 2014; Grötzinger et al 2014). Such studies focused on relevant microbial bioactivities, such as for example antibacterial activity (Sagar et al, 2013a, b; Moitinho-Silva et al 2014; Abdelmohsen et al 2014).…”
Section: Hypersaline Adapted Bacteria Inhabiting the Red Seamentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, diverse Red Sea associated microbiomes have been the focus of several recent studies at KAUST, including those from different environments: mangrove sediment (Al-Amoudi et al 2016a; Al-Amoudi et al 2016b; Alzubaidy et al 2016; Simões et al 2015), sea water (Qian et al 2011; Jimenez-Infante et al 2016), coral (Bayer et al 2013), sponge (Gao et al 2015; Tian et al 2014), and extreme niches such as Red Sea brine pools (Mwirichia et al 2016; Zhang et al 2015; Kamanda Ngugi et al 2015; Siam et al 2012; Abdallah et al 2014; Antunes et al 2015; Behzad et al 2016; Jimenez-Infante et al 2014; Grötzinger et al 2014). Such studies focused on relevant microbial bioactivities, such as for example antibacterial activity (Sagar et al, 2013a, b; Moitinho-Silva et al 2014; Abdelmohsen et al 2014).…”
Section: Hypersaline Adapted Bacteria Inhabiting the Red Seamentioning
confidence: 99%
“…Metagenomics studies of Red Sea samples show a distinctive composition of local microbiota, quite distinct from other marine environments (Thompson et al 2013). This is a specific consequence of the 25 Red Sea brine pools, thought to be inhospitable to organic life, harboring bacteria that thrive in these hydrothermal and hypersaline deep-sea environments (Mwirichia et al 2016; Zhang et al 2015; Kamanda Ngugi et al 2015; Grötzinger et al 2014; Siam et al 2012; Abdallah et al 2014; Antunes et al 2015; Behzad et al 2016; Jimenez-Infante et al 2014). An interesting study of vertical stratification was reported for two hydrothermal and hypersaline deep-sea pools in the Red Sea: the Atlantis II and Discovery.…”
Section: Hypersaline Adapted Bacteria Inhabiting the Red Seamentioning
confidence: 99%
“…Most recent study has developed the metagenomics for advanced characterization of microbial diversity from environmental sample. Behzad et al have also suggested that only a broad and representative metagenmic database could help to identify a dynamic modal of the microbiota that reside in different niches of the Red Sea [9]. In addition, the metagenomic database also revealed the majority of non-cultivable environmental strains and other unknown microbial sp., which were unexplored due to unstable cultivation conditions and other non-advanced techniques.…”
Section: Identification Of Microbial Communitiesmentioning
confidence: 99%
“…The enormous generated data also helped to identify a huge number of microbial genes, their mechanisms of adaptation, interaction within sp. and community, metabolite production and pathways as well as their pharmaceutical and biotechnology-based applications [9]. Therefore, direct metagenomic sequencing analysis of community DNA pools open the door for metatranscriptomics and metaproteomics analysis, and subsequently provided the related information to community physiology.…”
Section: Identification Of Microbial Communitiesmentioning
confidence: 99%
See 1 more Smart Citation